Antimicrobial property of bioactive factor isolated from Parmelia perlata - Thippeswamy, B; Sushma, N R; Naveenkumar, K J (International Multidisciplinary Research Journal, 2012)
Parmelia is previously mentioned in India Materia Medica as a treatment for a number of ailments and hence they are being used in large quantities as a food supplement in India. The crude hot extracts of Parmelia perlata and the isolated compounds were evaluated for their antimicrobial activity. The antibacterial activity of Parmelia perlata crude hot extracts revealed that the extracts showed significant effect against Clavibacter michiganensis (33 ± 0.06), moderate against Pseudomonas solanacearum (33 ± 0.32) and less potent against Escherichia coli (28 ± 0.10) when compared to the standard drug Streptomycin. The Fusarium oxysporum (26 ± 0.38) and Rhizopus nigricans (20 ± 0.06) were more susceptibility to wards the treatment of hot extracts, whereas Aspergillus niger (18 ± 0.15) demonstrated less susceptibility to crude hot extracts, but stardard antifungal drug bavistin was potent against all the fungal pathogens used in the study. Compound-I and compound-II isolated from the crude extract of Parmelia perlata showed efficient antibacterial activity. The antibacterial activity of compound-II was significant against to Clavibacter michiganensis (22 ± 0.17) and Pseudomonas solanacearum (44 ± 0.21), but less against to Escherichia coli (11 ± 0.17). Compound-I were more active against Pseudomonas solanacearum (31 ± 0.06) and moderately active against Clavibacter michiganensis (28 ± 0.05) and less active against to Escherichia coli (21 ± 0.23) when compared to Streptomycin. The antifungal activity of compound-II was better than compound-I. Compound-II was significant against Fusarium oxysporum (40 ± 0.05), Rhizopus nigricans (27 ± 0.02) and less active against to Aspergillus niger (18 ± 0.02) than compared to compound-I. The compound-I did not impotent against Aspergillus niger. The present investigation indicated that the crude hot extracts and the isolated compounds of Parmelia perlata have potential antimicrobial property.